Lal's commentary on the copyright Act, 1957( act 14 of 1957) with the copyright rules, 1958 and neighbouring rights also international copyright order, 1999 (Delhi, 2007)
The present Copyright Act was passed and enacted in 1957 by repealing the Indian Copyright Act, 1914 (3 of 1914) and the Copyright Act of 1911 passed by Parliament of the United Kingdom as modified in its application in India. The Indian Legislature felt that apart from the fact that U.K. Act did not fit in with the changed constitutional status of India
Keywords: "Copyright act, 1957"